Desorption reaction in MgH2 studied with in situ μ+SR. Issue 4 (14th February 2019) - Sugiyama, Jun; Umegaki, Izumi; Matsumoto, Mitsuru; Miwa, Kazutoshi; Nozaki, Hiroshi; Higuchi, Yuki; Noritake, Tatsuo; Forslund, Ola K.; Månsson, Martin; Cottrell, Stephen P.; Koda, Akihiro; Ansaldo, Eduardo J.; et al.
Abstract : To study the mechanism determining the desorption temperature of hydrogen storage materials, we have measured muon spin rotation and relaxation (μ + SR) in MgH2 together with the pressure in the sample space. Abstract : In order to study the mechanism determining the desorption temperature ( T d ) of hydrogen storage materials, we have measured positive muon spin rotation and relaxation (μ + SR) in MgH2 over a wide temperature range including its T d . The pressure in the sample cell due to desorbed H2 was measured in parallel with the μ + SR measurements under static conditions. Such in situ μ + SR measurements revealed that hydrogen starts to diffuse in MgH2 well below T d . This indicates the important role of hydrogen diffusion in accelerating the desorption reaction by removing the reaction product, i.e. H2, from the reaction system.